Offshore Wind Roadmap for the Philippines - World Bank (Washington, DC: World Bank, 2022)
This roadmap provides strategic analysis of the offshore wind development potential in the Philippines, considering the opportunities and challenges under different, hypothetical growth scenarios. The goal is to provide evidence to support the Government of the Philippines in establishing policy, regulations, processes, and infrastructure to enable successful growth of this new industry. The roadmap was initiated by the World Bank country team in the Philippines under the umbrella of the World Bank Group’s (WBG’s) Offshore Wind Development Program—which aims to accelerate offshore wind development in emerging markets—and was funded by the Energy Sector Management Assistance Program (ESMAP) in partnership with the International Finance Corporation (IFC).